Analisis Kebutuhan Siswa Terhadap Pengembangan Modul Elektronik Berbasis Scientific Reading Based Project untuk Meningkatkan Kemampuan Literasi Sains - Restiani, Ning Dainty; Suryandari, Kartika Chrysti; Salimi, Moh. (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Science literacy is one of the essential competencies of the 21st century that needs to be instilled since elementary school level. However, the facts on the ground show that students' science literacy is still relatively low due to limited learning media and lack of age-appropriate scientific readings. This study aims to analyze the need for developing an electronic module based on the Scientific Reading Based Project (SRBP) that can support the improvement of science literacy. The method used is descriptive qualitative with instruments in the form of questionnaires and interviews with fifth grade students from three elementary schools. Data were analyzed based on six aspects of needs, namely: learning materials, student involvement, methods and media, scientific reading, technology, and evaluation. The results of the study show that the aspects of the need for scientific reading, the use of technology, and the development of project-based teaching materials received a high response. On the other hand, active student participation and the use of learning media are still limited. These findings provide a strong basis for designing an electronic SRBP module that is contextual, interesting, and in accordance with student needs.Literasi sains merupakan salah satu kompetensi esensial abad ke-21 yang perlu ditanamkan sejak jenjang sekolah dasar. Namun, fakta di lapangan menunjukkan bahwa literasi sains siswa masih tergolong rendah karena keterbatasan media pembelajaran dan kurangnya bacaan ilmiah yang sesuai usia. Penelitian ini bertujuan untuk menganalisis kebutuhan pengembangan modul elektronik berbasis Scientific Reading Based Project (SRBP) yang dapat mendukung peningkatan literasi sains. Metode yang digunakan adalah deskriptif kualitatif dengan instrumen berupa angket dan wawancara terhadap siswa kelas V dari tiga sekolah dasar. Data dianalisis berdasarkan enam aspek kebutuhan, yaitu: materi pembelajaran, keterlibatan siswa, metode dan media, scientific reading, teknologi, dan evaluasi. Hasil kajian menunjukkan bahwa aspek kebutuhan terhadap bacaan ilmiah, penggunaan teknologi, dan pengembangan bahan ajar berbasis proyek mendapat respon tinggi. Sebaliknya, partisipasi aktif siswa dan penggunaan media pembelajaran masih terbatas. Temuan ini memberikan dasar yang kuat untuk merancang modul elektronik SRBP yang kontekstual, menarik, dan sesuai dengan kebutuhan siswa.